Landscape of IP Ownership and Revenue Sharing Policies in India and their benchmarking with policies in the West (Global Journal of Science Frontier Research, 2018)
Innovation is the key to sustainable ecosystem in Science and Technology (S&T). Robust Intellectual property (IP) policies and revenue sharing models to incentivise innovators are imperative to boost creativity and innovation by them. This paper assesses the current IP ownership and revenue sharing policies in India deployed by key autonomous public research institutes (PRIs) under Ministry of S&T (DBT, CSIR, ICMR, ICAR), Ministry of Defence (DRDO), and Ministry of Agriculture and Farmers Welfare (ICAR), Government of India (GOI) with 345 institutes under their purview and top 100 universities as per National Institutional Ranking Framework (NIRF)-2017 issued by GOI. Pertinent IP policy typologies studied included presence/absence of IP policies, IP ownership policies, type of revenue sharing models, benefit sharing policies, payout frequency, start-up policies etc. and its bench marking with successful models being followed by leading universities in west in USA, UK and Canada. The findings of this study will be of relevance to policy makers for understanding policy typology, to practitioners for drafting suitable policies and to innovators as key beneficiary of such policies.